Characteristics of pigments, modification, and their functionalities. Issue 3 (20th February 2019) - Sarkodie, Bismark; Acheampong, Collins; Asinyo, Benjamin; Zhang, Xun; Tawiah, Benjamin
Abstract: Novel treatments of pigments with inorganic materials have tremendous industrial and commercial prospects. Specific treatment of pigment has a marked effect on its behavior during application. The treatment allows a broad modification of the surface characteristics of pigment particles which leads to improved functionalities. Surface modification of pigments is achieved via coating, polymerization with modifying reagent, treatment with derivatives or polymers, which alter either the optical, conductivity or dispersibility during processing and application. These and many other distinguishing factors that affect the characteristics of pigments such as the class, crystal structure, particle morphology, particle size, hiding power, pigment volume concentration, surface character, and surface treatment have been reviewed. Various organic pigments such as those from fungus and bacteria, and the various families of pigment types such as metallic pigment, light interference, and diffractive pigments which presents decorative quality such as leafing, nonleafing, pearlscent, and Fabry‐Perot effects on substrates have also been reviewed in addition to those from inorganic sources with emphasis on the structure and physiochemical modifications using metal and nonmetal Ions.